Setting Targets for HIV: An Evaluation of Indicator Quality and Target Achievement in National Strategic Plans. (1st December 2017) - Sharp, Alana; O'Hagan, Richael; Honermann, Brian; Millett, Gregorio
Abstract : Background: National Strategic Plans (NSPs) for HIV have become foundational documents that frame responses to HIV. Both Global Fund and PEPFAR require coordination with NSPs as a component of their operations. Despite the role of NSPs in country planning, no rigorous assessment of NSP targets and performance outcomes exists. We performed a quantitative analysis of the quality of NSP indicators and targets and assessed whether historical NSP targets had been achieved. Methods: All targets and indicators from publicly available NSPs from 35 countries are coded as structural, input, output, or impact indicators. Targets were evaluated for specificity, measurability, achievability, relevance, and being time-bound. In addition, progress toward achieving targets was evaluated using historical NSPs from 4 countries. Results: NSPs emphasized output indicators, but inclusion of structural, input, or impact indicators was highly variable. Most targets lack specificity in target population, numeric baselines or targets, and a data source for monitoring. Targets were, on average, 205% increases or decreases relative to baselines. Alignment with international indicators was variable. Metrics of indicator quality were not associated with NSP funding needs. Monitoring of historical NSP targets was limited by a lack of defined targets and available data. Conclusions: Country NSPs are limited by a lack of specific, measurable, and achievable targets. The low achievement of targets in historical NSPs corroborates that targets are often poorly defined and aspirational, and not linked to available data sources. NSP quality may be improved through better use of programmatic data and greater inclusion of targets for process measures.